Financial Performance Analysis of PT. Bank Syariah Indonesia (BSI) for the 2021-2022 Period Using the Camel Method - Nasution, Sariati; Yafiz, Muhammad; Anggraini, Tuti (Sharia Economics Department Universitas KH. Abdul Chalim, Mojokerto, 2023)
The purpose of this research is to analyze the financial performance of PT. Bank Syariah Indonesia for the 2021-2022 period using the CAMEL method. This study uses descriptive quantitative methods and uses secondary data. The results of this study are that in 2021 CAR PT. Bank Syariah Indonesia is in the range of 22.09% and in 2022 CAR PT. Bank Syariah Indonesia is in the range of 20.29%. In general, in 2021 and 2022 the CAR value of PT. Bank Syariah Indonesia is classified as healthy because it meets the standards set by Bank Indonesia. In 2021 the KAP ratio of PT. Bank Syariah Indonesia is in the range of 0.015% and in 2022 the ratio of KAP PT. Bank Syariah Indonesia is in the range of 0.045%. In general, in 2021 and 2022 the KAP value of PT. Bank Syariah Indonesia is classified as healthy because it meets the standards set by Bank Indonesia. In 2021 NPF of PT. Bank Syariah Indonesia is in the range of 0.87% and in 2022 the NPF of PT. Bank Syariah Indonesia is in the range of 0.57%. In general, in 2021 and 2022 the NPF value of PT. Bank Syariah Indonesia is classified as healthy because it meets the standards set by Bank Indonesia. In 2021 ROA PT. Bank Syariah Indonesia is in the range of 1.61% and in 2022 PT. Bank Syariah Indonesia is in the range of 1.98%. In general, in 2021 and 2022 the ROA value of PT. Bank Syariah Indonesia is classified as healthy because it meets the standards set by Bank Indonesia. In 2021 FDR PT. Bank Syariah Indonesia is in the range of 73.39% and in 2022 FDR PT. Bank Syariah Indonesia is in the range of 79.37%. In general, in 2021 and 2022 the FDR value of PT. Bank Syariah Indonesia is classified as healthy because it meets the standards set by Bank Indonesia.